2009
DOI: 10.1021/om9006278
|View full text |Cite
|
Sign up to set email alerts
|

A Cation-Captured Palladium(0) Anion: Synthesis, Structure, and Bonding of [PdBr(PPh3)2] Ligated by an N-Heterocyclic Phosphenium Cation

Abstract: Unsaturated N-heterocyclic phosphenium cations (uNHP) stabilize the [Pd 0 (PR3)2X] -anion proposed over the past decade to be the crucial but elusive intermediate in palladium-catalyzed cross-coupling reactions (X = halide). Insertion of metal into the PBr bond of the precursor mesityl-substituted bromophosphine gives the structurally characterized Pd(0)-phosphenium complex (uNHPMes)Pd(PPh3)2Br, which features a long Pd-Br bond (2.7240(9)Å) and the shortest known Pd-P bond (2.1166(17)Å). The reaction is propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
49
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 26 publications
4
49
0
Order By: Relevance
“…We assume that this reaction is likewise initiated by Cl/OTf exchange, but that a hypothetical NHP palladium(0) triflate is unstable and decomposes. This finding is in line with previous results,5,13 which indicated that the “push–pull” effect exerted by a combined action of π‐acceptor and strong σ‐donor ligands is essential for the stabilization of the zero‐valent metal atom in these complexes.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…We assume that this reaction is likewise initiated by Cl/OTf exchange, but that a hypothetical NHP palladium(0) triflate is unstable and decomposes. This finding is in line with previous results,5,13 which indicated that the “push–pull” effect exerted by a combined action of π‐acceptor and strong σ‐donor ligands is essential for the stabilization of the zero‐valent metal atom in these complexes.…”
Section: Resultssupporting
confidence: 93%
“…The 31 P chemical shifts of 3 – 6 in general fall in the downfield region ( δ > 200 ppm), which is typical of the majority of related phosphenium complexes59 but not for IIb , which exhibits a very unusual 31 P chemical shift at δ = 26.9 ppm,7 nearly 200 ppm lower than in the other complexes. We attribute this amazing deviation to the rather special electronic situation7 that presumably makes this compound an outlier.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Both the unusual reaction pathway and the possibility to observe the reaction intermediate 8 are again to a large extent attributable to the strong prepolarization of the P-Cl bond in the starting chloro-NHP. A similar formation of a cation-captured Pd(0)-bromide was recently also observedduring the reaction of a P-bromo-NHP with tetrakis-triphenylphosphine palladium(0) 21. …”
supporting
confidence: 76%